The Enigmatic Thelebolaceae (Thelebolales, Leotiomycetes): One New Genus Solomyces and Five New Species - Zhang, Zhiyuan; Dong, Chunbo; Chen, Wanhao; Mou, Quanrong; Lu, Xiaoxiao; Han, Yanfeng; Huang, Jianzhong; Liang, Zongqi (Frontiers in Microbiology, 2020)
The family Thelebolaceae belongs to the order Thelebolales, class Leotiomycetes, and contains 22 genera. In this study, we introduce a new genus Solomyces gen. nov. in the family Thelebolaceae, which is supported by morphological observation and multilocus-based (ITS+LSU and ITS+LSU+MCM7+EF1A+RPB2) phylogenetic analysis. Maximum-likelihood and Bayesian phylogenetic inference analyses indicated that Solomyces is a distinct genus within this family. The new genus is compared against related Thelebolaceae genera and its description and illustration are provided. This genus comprises one new species and one unnamed species (included two strains). We also report the addition of four new species—Pseudogymnoascus shaanxiensis, P. guizhouensis, P. sinensis, and Geomyce obovatus—in the family Thelebolaceae, and present their morphological and phylogenetic characterization.